Analysis of Grounding Resistance Performance with Effect of Conductive Compound Medium - Ahmad, Muhamad Faiz Hakimi; Mohd Jamail, Nor Akmal; Qamarul Ezani Kamarudin (Evolution in Electrical and Electronic Engineering, 2025)
Grouding stsrem is the most crucial area in power system network. Poor grounding system can be dangerous to the users and wire of the electrical distribution system in the event of electrical fault. To prevent this accident, it is very important to have a good grounding system to protect the systems well as to the user. Therefore, this paper measures the grounding resistance with two planted electrode designs with two different conductive compound using Driven Rod method with the help of equipment earth testers. The experimental works was conducted in two medium of conductive compound which is graphite and bentonite using standard and three branches copper rod. The experimental results show that the copper rod with conductive compound suitable to replace the standard copper rod since the measured grounding resistance is the lowest. It is also proven that the three branches copper rod exhibits better value of soil resistaivity which can be used for the grounding system.